Impact of DSM-5 PTSD and gender on impaired eating behaviors in 512 Italian earthquake survivors. Issue 1 (30th January 2015) - Carmassi, Claudia; Antonio Bertelloni, Carlo; Massimetti, Gabriele; Miniati, Mario; Stratta, Paolo; Rossi, Alessandro; Dell׳Osso, Liliana
Abstract: Considerable comorbidity rates between Post-traumatic Stress Disorder (PTSD) and eating disorders have been recently reported, as well as increased obesity and underweight conditions. The aim of the present study was to investigate the possible associations between DSM-5 PTSD, gender and impaired eating habits in a sample of 512 Italian earthquake survivors evaluated by the Trauma and Loss Spectrum-Self Report (TALS-SR) and the Mood Spectrum-Self Report (MOODS-SR). Alterations in eating behaviors were assessed by means of four MOODS-SR items: n =150 (…there was no food that appealed to you or tasted good to you?), n =151 (…you constantly craved sweets or carbohydrates?), n =152 (…your appetite or weight decreased?), n =153 (…your appetite or weight increased?). In a Decision Tree procedure subjects with PTSD with respect to those without and, in the No-PTSD subgroup, females with respect to males, had a significantly higher ratio of at least one MOODS-SR eating behavior item (MOODS-SR EB). In the No-PTSD subgroup only, subjects with at least one MOODS-SR EB presented a significantly higher mean TALS-SR symptomatological domains total score with respect to those without MOODS-SR EB. In conclusion, alterations in eating behaviors were associated with PTSD after the L׳Aquila earthquake; among survivors without PTSD significant a correlation emerged between MOODS-SR EB and PTSD symptoms. Highlights: Significant eating habits alterations in 512 earthquake survivors with DSM-5 PTSD. Significant gender differences in survivors without DSM-5 PTSD: F > M . Significantly more PTSD symptoms in no DSM-5 PTSD survivors with eating alterations.